Giant adrenal myelolipomas: a literature review - Mircea Hogea; Anda Hogea; Marius Moga; Roxana Dragomir; Simona Grigorescu; Bogdan Socea (Journal of Mind and Medical Sciences)
Myelolipomas are described as small tumors, with some authors referring to sizes less than 4 cm in diameter. However, when greater than 10 cm, myelolipomas are labeled as giant tumors and thus, have a definite indication for surgical resection. Myelolipomas represent a small percentage of adrenal tumors. Giant myelolipomas are usually discovered incidentally during imaging studies performed for other conditions. They are often slow-growing and may reach sizes that significantly distort the anatomy of the affected area. Despite their large size, they are usually benign and do not spread to other parts of the body. Adrenal myelolipoma is a benign tumor with a scarce number of detailed cases reported in literature. It is frequently discovered by chance, covering a variety of differential diagnoses. Imaging techniques and histopathological examinations are of great importance in the differential diagnosis of adrenal gland lesions, including retroperitoneal lipoma and liposarcoma, adrenal myelolipoma, adrenal lymphoma, adrenal adenoma, adrenocortical carcinoma, pheochromocytoma or metastasis. We performed a comprehensive review on PubMed of all cases of giant adrenal myelolipoma reported in literature with more than 10 cm in diameter, in order to estimate the incidence, diagnosis and treatment of giant myelolipoma. So far, only 15 cases of truly giant adrenal myelolipoma have been reported between 1981 and 2023.